Analysis of Calmness Training for Archery Sports for PORPROV Athletes in Malang Regency - Ratno Susanto, Ratno Susanto; Anggraeni, Dwi Cahyati; Taroreh, Bangkit Seandi; Afandi, Achmad (JUMORA: Jurnal Moderasi Olahraga, 2025)
The purpose of this study is to examine how calmness training affects archery competitors' performance as they get ready for the Malang Regency Provincial Sports Week (PORPROV). Calmness training, which incorporates breathing exercises, meditation, and visualization, is thought to help athletes become more focused and mentally calm, which in turn improves their accuracy when firing an archer. Twenty archery athletes from Malang Regency served as research samples for this study, which employed an experimental design with a pre-test and post-test methodology. Tests of shooting accuracy, anxiety surveys, and in-person observations of athlete behavior during practice and competition simulations were used to gather data. According to the findings, the athlete's shooting accuracy significantly improved from 60% to 82% after completing the tranquility training program for four weeks. Moreover, athletes' anxiety levels declined, with an average score falling from 60% to 40%. These modifications show that calmness training helps archery players perform better technically, focus better, and experience less anxiety. Based on the study's findings, it can be said that calmness training helps archery athletes perform better and ought to be a regular component of the training regimen for archery athletes in Malang Regency, particularly when they're getting ready for events like PORPROV